Political Will Of The Indonesian Government In Addressing Data Leakage And Cybersecurity In The Era Of Digital Transformation - Safrida Nurulita; Ridwan (UNIVERSITAS PAKUAN, 2025)
Technological development requires everyone to carry out activities in cyberspace. Cybercriminals exploit the exchange of information to steal important data, which indirectly contributes to data leakage. Indonesia is one of the countries with the most internet users in the world and often experiences data leaks. Therefore, the risk of cyber threats coincides with technological use. This research discusses the extent of the Indonesian government's political will to overcome cyber threats. The research method used is a descriptive qualitative type that uses Brinkerhoff's political will theory. The results show that the Indonesian government is strongly committed to overcoming cybersecurity threats and data leaks through the establishment of the BSSN institution and coordination with various parties. However, weak security awareness among policymakers and the public, gaps in cybersecurity education and understanding, budget limitations, weak cybersecurity systems, and sectoral egos present challenges to strengthening cybersecurity in Indonesia and cause data leaks. Thus, the government's concrete steps to establish the Cyber Security and Resilience Bill are expected to fill the regulatory vacuum so that the implementation of cyber security policies can be optimized. Increasing government security awareness, prioritizing the cybersecurity budget, ensuring the availability of competent resources, conducting well-coordinated efforts, providing education, and encouraging active community involvement are solutions that can protect data from growing threats. Keywords: political will; cybersecurity; data leakage